Anatomical Proposal for Botulinum Neurotoxin Injection Targeting the Platysma Muscle for Treating Platysmal Band and Jawline Lifting: A Review - Yi, Kyu-Ho; Lee, Ji-Hyun; Lee, Kangwoo; Hu, Hye-Won; Lee, Hyung-Jin; Kim, Hee-Jin (Toxins, 2022)
The platysma muscle is a thin superficial muscle that covers the entire neck and lower part of the face. The platysma muscle is the primary target muscle for botulinum neurotoxin injection therapy aimed at treating platysmal band and lower facial lifting. In the procedure of botulinum neurotoxin injection therapy, a lack of knowledge of the anatomy of the platysma muscle and the properties of botulinum neurotoxin can lead to side effects such as dysphagia, dysphonia, and weakness of the neck muscles. Anatomically safe injection sites have been proposed for the platysma muscle, and the appropriate injection technique has been reviewed. We proposed optimal injection sites based on the external anatomical features of the mandible. The aim of these proposal was to standardize the procedure for the effective use of botulinum neurotoxin injections by minimizing the dose unit and injection points and thereby preventing adverse events.